2022
DOI: 10.3390/antibiotics11070961
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Reverts Tolerance and Restores Susceptibility to Chlorhexidine and Benzalkonium in Gram-Negative Bacteria, Gram-Positive Bacteria and Yeasts

Abstract: The spread of microorganisms causing health-care associated infection (HAI) is contributed to by their intrinsic tolerance to a variety of biocides, used as antiseptics or disinfectants. The natural monomeric stilbenoid resveratrol (RV) is able to modulate the susceptibility to the chlorhexidine digluconate (CHX) biocide in Acinetobacter baumannii. In this study, a panel of reference strains and clinical isolates of Gram-negative bacteria, Gram-positive bacteria and yeasts were analyzed for susceptibility to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recently, there has been demonstration of reversing biocide resistance by harnessing the synergistic activity of Resveratrol and some biocides as reported by Migliaccio et al [ 64 ], in bacteria including K. pneumoniae . Understanding biocide resistance is key in finding sustainable solutions to control biocide tolerant/resistant K. pneumoniae .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been demonstration of reversing biocide resistance by harnessing the synergistic activity of Resveratrol and some biocides as reported by Migliaccio et al [ 64 ], in bacteria including K. pneumoniae . Understanding biocide resistance is key in finding sustainable solutions to control biocide tolerant/resistant K. pneumoniae .…”
Section: Resultsmentioning
confidence: 99%
“…A recent in vitro study highlighted that RSV, chlorhexidine digluconate (CHX), and benzalkonium chloride (BZK) co-administration could be successfully applied against nosocomial pathogens responsible for healthcare-associated infections, such as Burkholderia spp., K. pneumoniae, P. aeruginosa, Stenotrophomonas maltophilia, and Candida albicans clinical isolates [245].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…In S. aureus, bacteriostatic activity is described for this compound with no detection of resveratrol-induced membrane damage [19,21]. Moreover, resveratrol has increased the susceptibility of several Gram-negative and Gram-positive bacteria, including S. aureus, and yeasts to chlorhexidine and benzalkonium chloride, or to streptomycin and ciprofloxacin in multidrug-resistant Gram-negative species, and enhanced the efficacy of aminoglycosides against S. aureus, suggesting its potential as an EPI [21][22][23]. In fact, some studies report that this compound may act as an inhibitor of efflux pumps, as suggested for Escherichia coli, Acinetobacter baumannii and Arcobacter species [20,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%